Spin-phonon interaction and mode softening in NiF2: Магнетизм - Lockwood, D. J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The temperature dependence of the four Raman-active phonons in NiF2 has been investigated at temperatures above and below the antiferromagnetic ordering temperature of TN=73 K. All four modes exhibit distinct anomalies in their intensities and frequencies near TN due to spin-phonon coupling. The phonon linewidths also exhibit weak anomalies. From the temperature dependences of the phonon frequencies, estimates are made of the spin-phonon coupling coefficients. The B1g phonon exhibits anomalous mode softening with decreasing temperature from 300 K to TN .